Installation of an Artificial Vegetating Island in Oligomesotrophic Lake Paro, Korea - Eun-Young Seo; Oh-Byung Kwon; Seung-Ik Choi; Ji-Ho Kim; Tae-Seok Ahn (The Scientific World Journal)
After cut off of inflowing water, Lake Paro, an oligomesotrophic lake lost littoral zone, an important region for the aquatic ecosystem. For the first step of restoration, the artificial vegetation island was installed. The concentration of nutrients in lake water was not sufficient for the growth of macrophyte as total phosphate was ranged from 58 to 83 μg L−1. In order to overcome this problem, the hydrophobic substratum for bacterial attachment was selected as buoyant mat material of the artificial vegetation island. In this medium, total phosphate and total nitrogen were ranged from 190 to 1,060 μg L−1 and from 4.9 to 9.1 mg L−1, respectively. These concentrations were high enough for macrophytes growth. After launching 1,800 m2 of AVI in Lake Paro, the macrophytes, Iris pseudoacorus and Iris ensata, grew well after five years of launching without the addition of fertilizer. Furthermore, fishes were plentiful under the artificial vegetation island, and ducks were observed on the artificial vegetation island. Bacteria using sunlight as energy source and self-designed ecotechnology can be used as an alternative method for the restoration of disturbed littoral zone in oligo-mesotrophic lakes.